Diagnosing autism in a clinical sample of adults with intellectual disabilities: How useful are the ADOS and the ADI-R? - Sappok, T.; Diefenbacher, A.; Budczies, J.; Schade, C.; Grubich, C.; Bergmann, T.; Bölte, Sven; Dziobek, I. (Pergamon Press, 2013)
Intellectual disability (ID) and autism spectrum disorder (ASD) are frequently co-occurring conditions. Carefully diagnosing ASD in individuals with ID would allow for more tailored clinical interventions that would improve mental health and quality of life. In this study, we evaluated the psychometric properties of the Autism Diagnostic Observation Schedule (ADOS) and the Autism Diagnostic Interview-Revised (ADI-R) in a clinical sample of 79 adults with ID who were suspected of also having ASD. In the testable cases (68%), the ADOS was over-inclusive (specificity 45%) but highly sensitive (100%) of ASD. In the ADI-R, the feasibility was 37%, with a sensitivity of 88% and a specificity of 80%. Previously proposed adaptations of the ADOS algorithm were evaluated, and new items and tasks were suggested. The ADOS and the ADI-R were found to be valuable diagnostic tools for adults with ID. Adjustments of the setting and the tasks may further improve their feasibility and specificity.